MEASURES TO INCREASE THE CAPACITY OF THE TRACK SECTION OF THE DRIENOVSKÁ NOVÁ VES – KYSAK RAILWAY LINE (Perner's Contacts, 2024)
Railway transport is a continuous process that must be coordinated at all levels of management and is determined by technological procedures. From a technological point of view, it is important to correctly determine the practical throughput performance of the track section, also called the capacity of the railway infrastructure. This means which railway transport can be used to load the track section so that it exhibits sufficient railway transport stability even during operational irregularities. The article is focused on the method of increasing the capacity of the track section Drienovská Nová Ves - Kysak using the method of determining the practical throughput performance in the anticipated timetable. The detailed determination of the occupation times of the section in the current state and in the application of individual proposals provides us with information about other possibilities for the modernization of the railway infrastructure in the Slovak Republic. The article describes and evaluates the advantages and disadvantages of individual proposals for increasing the capacity of the examined track section. As part of the future modernization of the railway infrastructure of this track section, it is necessary to implement these measures, as the examined line section is part of the RFC corridor. The intention is not only to increase the quality of railway infrastructure, but also the quality of freight and passenger transport.
Keywords: Railway traffic; Capacity; Modernization; Railway Infrastructure